Role of politically motivated internet addiction and ideological passion in linking college student's mental health education and wellbeing - Meng, Shuyu (Frontiers in Psychiatry, 2022)
College students are increasingly reporting common mental health issues like depression and anxiety, raising severe concerns for students' psychological wellbeing. Specifically, after the emergence of Post-COVID-19, digitization caused a potential role in mitigating students' psychological concerns. Therefore, the role of mental health education has been regarded as a topic of interest in managing the issue of Chinese college students' mental wellbeing. This study intends to look into the relationship between mental health education and psychological wellbeing, along with the moderating role of politically motivated internet addiction and the ideological passion of college students. For the given reason, the random sampling method was employed for collecting data from target respondents. The study uses 750 questionnaires prepared on a five-point Likert scale that were distributed to the respondents with an expected response rate of 50%. The partial least square (PLS) software was used to analyze the data for this study. The study concludes that there is a significant moderating role of politically motivated internet addiction and ideological passion in the relationship between college students' mental health and wellbeing. The study meaningfully contributes to the body of knowledge by establishing the unique, positive moderating role of Politically motivated internet addition in strengthening the relationship which undoubtedly will assist in improving the psychological wellbeing of college students through mental health education policies and implications.